Update on the pharmacology of calcitonin/CGRP family of peptides: IUPHAR Review 25. (28th November 2017) - Hay, Debbie L; Garelja, Michael L; Poyner, David R; Walker, Christopher S
Abstract : The calcitonin/CGRP family of peptides includes calcitonin, α and β CGRP, amylin, adrenomedullin (AM) and adrenomedullin 2/intermedin (AM2/IMD). Their receptors consist of one of two GPCRs, the calcitonin receptor (CTR) or the calcitonin receptor‐like receptor (CLR). Further diversity arises from heterodimerization of these GPCRs with one of three receptor activity‐modifying proteins (RAMPs). This gives the CGRP receptor (CLR/RAMP1), the AM1 and AM2 receptors (CLR/RAMP2 or RAMP3) and the AMY1, AMY2 and AMY3 receptors (CTR/RAMPs1–3 complexes, respectively). Apart from the CGRP receptor, there are only peptide antagonists widely available for these receptors, and these have limited selectivity, thus defining the function of each receptor in vivo remains challenging. Further challenges arise from the probable co‐expression of CTR with the CTR/RAMP complexes and species‐dependent splice variants of the CTR (CT(a) and CT(b) ). Furthermore, the AMY1(a) receptor is activated equally well by both amylin and CGRP, and the preferred receptor for AM2/IMD has been unclear. However, there are clear therapeutic rationales for developing agents against the various receptors for these peptides. For example, many agents targeting the CGRP system are in clinical trials, and pramlintide, an amylin analogue, is an approved therapy for insulin‐requiring diabetes. This review provides an update on the pharmacology of the calcitonin family of peptides by members of the corresponding subcommittee of the International Union of Basic and Clinical Pharmacology and colleagues.